Seed Germination and Development of Serapias vomeracea (Burm.fil.) Briq. ssp orientalis Greuter in Tissue Culture - Cevdet, Gumus; Sebnem, Ellialtioglu; Gümüş, Cevdet (Research Journal Biotechnology, 2012)
Serapias vomeracea (Burm. fil.) Briq. ssp. orientalis Greuter plants were obtained via asymbiotic germination under in vitro conditions. For the germination of seeds, different doses of gibberellic acid (GA3) (0, 0.1 and 0.5 mg/L) were added into a basic nutrient media consisting of half-strength MS (1/2 MS), Van Waes and DeBergh (VW and DB), Knudson C and non-inorganic nitrogen Knudson C (KC-N). Cultures were incubated in darkness for the first 3 months and thereafter transferred to a light/dark photoperiod of 16:8. At the end of the third month, protocorm rates were identified. They were subcultured every 4 weeks and 1/2 MS medium was used as a transfer medium. The highest germination rate, protocorm rate and plant growth rate were obtained from the Knudson C medium. The germination rate and number of plantlets were affected negatively by adding GA3.
Keywords: Orchid; Germination; Serapias Vomeracea; Medium